KONTRIBUSI LEMBAGA KEUANGAN MIKRO SYARIAH DALAM MENINGKATKAN PERTUMBUHAN BISNIS DI KOTA KEDIRI STUDI PADA BMT UGT NUSANTARA CABANG KEDIRI - Nabbila, Faricha Lita; Sulistyowati (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
Islamic microfinance is a new strategy for economic development that is intended to help low-income people who have not been touched by financial goods and services (unbankable). Islamic microfinance can play an important role in community empowerment and poverty alleviation by facilitating access to financial goods and services. The importance of economics and microfinance to the Indonesian economy is undeniable. MSMEs, for example, are able to absorb more than 90% of the national workforce and contribute 60.34% of GDP. In this study, qualitative techniques using descriptive research were applied. The research data comes from interviews with related parties, including the Head of BMT UGT Sidogiri KCP Kediri. In this research, data analysis includes data reduction, data presentation, and conclusion drawing. Based on the findings of the study, BMT UGT Nusantara Kediri made a significant contribution to business growth in the City of Kediri.